Cities for people - Gehl, Jan, ....- (Washington : Island Press, 2010)
For more than forty years Jan Gehl has helped to transform urban environments around the world based on his research into the ways people actually use--or could use--the spaces where they live and work. In this revolutionary book, Gehl presents his latest work creating (or recreating) cityscapes on a human scale. He clearly explains the methods and tools he uses to reconfigure unworkable cityscapes into the landscapes he believes they should be: cities for people. The book is extensively illustrated with over 700 photos and drawings of examples from Gehl's work around the globe.
Keywords: Architectuur; Sociologie; Stadsontwikkeling; Stedenbouw